Parametric Programming of Multi-Type Holes Using the Improved Genetic Algorithm - Tai Yong, Wang; Gao, Shan; Zhang, Yong Bin; Shen, Teng Yue; Dong, Jia Jia; Ding, Yan Yu (Key engineering materials, 2018)
For path planning and program generation of multi-type holes, this paper presents a method of the path planning, by using the improved genetic algorithm based on chaos algorithm, and develops an interactive programming system for multi-type holes. Users can choose regular holes, and input the parameters and the necessary information, according to their needs. Then the system will combine holes automatically, and calculate the position coordinates of each hole. After that the path planning is carried out by using the improved genetic algorithm. Finally, the system carries out the simulation experiment of the path planning, and outputs NC program. Experiment shows the system can realize the path planning of multi-type holes by a combination of regular holes and generate the NC code after path planning. The optimization of path is better and the operation is more convenient than UG and other professional CAM software.